MODEL PEMBELAJARAN GERAK DASAR ATLETIK BERNUANSA THE JUNGLE SURVIVOR BERBASIS ALAT MODIFIKASI SEDERHANA (LOW-COST) PADA SISWA SEKOLAH DASAR - Rany Ade Akhsanu Nadiyah; Yusuf Hanafi; Anang Marzuqi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was based on the limited availability of facilities and students’ boredom with learning basic track and field movements such as running, jumping, and throwing. The objective of this study is to develop an innovation using a basic track and field movement learning model based on an adventure circuit themed “The Jungle Survivor,” utilizing low-cost materials, and presented in the form of a Teacher’s Guidebook and instructional demonstration videos. The method used in this R&D study modified the ADDIE framework into the ADDE model (Analysis, Design, Development, Evaluation) due to time constraints. The research results showed a feasibility percentage of 92.86%, meeting the criterion of “highly valid” based on assessments by media experts and subject matter experts. Thus, this adventure circuit product based on modified equipment was deemed highly suitable for use as an effective alternative medium to enhance students’ enthusiasm for learning while creating a more engaging and interactive athletics learning experience.